Alternative causal inference methods in population health research: Evaluating tradeoffs and triangulating evidence. (April 2020) - Matthay, Ellicott C.; Hagan, Erin; Gottlieb, Laura M.; Tan, May Lynn; Vlahov, David; Adler, Nancy E.; Glymour, M. Maria
Abstract: Population health researchers from different fields often address similar substantive questions but rely on different study designs, reflecting their home disciplines. This is especially true in studies involving causal inference, for which semantic and substantive differences inhibit interdisciplinary dialogue and collaboration. In this paper, we group nonrandomized study designs into two categories: those that use confounder-control (such as regression adjustment or propensity score matching) and those that rely on an instrument (such as instrumental variables, regression discontinuity, or differences-in-differences approaches). Using the Shadish, Cook, and Campbell framework for evaluating threats to validity, we contrast the assumptions, strengths, and limitations of these two approaches and illustrate differences with examples from the literature on education and health. Across disciplines, all methods to test a hypothesized causal relationship involve unverifiable assumptions, and rarely is there clear justification for exclusive reliance on one method. Each method entails trade-offs between statistical power, internal validity, measurement quality, and generalizability. The choice between confounder-control and instrument-based methods should be guided by these tradeoffs and consideration of the most important limitations of previous work in the area. Our goals are to foster common understanding of the methods available for causal inference in population health research and the tradeoffs between them; to encourage researchers to objectively evaluate what can be learned from methods outside one's home discipline; and to facilitate the selection of methods that best answer the investigator's scientific questions. Highlights: Differences in methodological training inhibit interdisciplinary collaboration. Most nonrandomized causal studies are confounder-control or instrument-based. All methods involve untestable assumptions and tradeoffs in precision and validity. The preferred approach depends on the limitations of previous work in the area.